Design and application of mine integration dispatching communication system - XUE Xiaoyan; HUO Zhenlong; GU Jun (Gong-kuang zidonghua, 2016)
In view of problem that most mine communication systems scattered, and could not cross the others for scheduling command, a mine integration dispatching communication system was designed, and composition and functions of the system were introduced. The practical application results show that the system can be compatible with existing coal mine communication system, provide efficient business platform and bridge to leapfrog communication among each system, and effectively improve mine emergency scheduling disposal ability and management level of coal mine safety production.